Heart disease prediction system - Amit, Tayab Al Azad; Fullkoli, Raida Nawar; Palit, Niloy; Nafisa, Farhana Khan; Binoy, MD Muntakim Ahmed (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.